Empirical finance - Shigeyuki Hamori (Journal of Risk and Financial Management, 2020)
The research field related to finance has made great progress in recent years due to the development of information processing technology and the availability of large-scale data. This special issue is a collection of 16 articles on empirical finance and one book review. The content is six articles on machine learning, five articles based on traditional econometric analysis, and five articles on emerging markets. The large share of articles on the application of machine learning is in line with recent trends in finance research. This special issue provides a state-of-the-art overview of empirical finance from economic, financial, and technical points of view.
Keywords: 330; artificial intelligence; emerging markets; financial econometrics; machine learning